2022
DOI: 10.1037/hea0001151
|View full text |Cite
|
Sign up to set email alerts
|

Associations between behavioral flexibility and health behavior in cardiac patients in the Do CHANGE trials.

Abstract: Objective: Health behaviors (e.g., physical inactivity, poor diet) are associated with poor prognosis and mortality in cardiac patients. Changing these behaviors is challenging and only a minority of patients succeeds in this endeavor. Studies show that behavioral flexibility (defined as responding less habitually to stimuli and having a large behavioral repertoire) is a potentially important facilitator of health behaviors. The current study examines the association between behavioral flexibility and health b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Our field has identified novel behavioral and psychosocial risk and prognostic factors for multiple CVD presentations and plausible mechanisms through which these factors could influence the development and course of CVD. Examples that reflect the ongoing evolution and expansion of the field’s focus are the articles in this issue on posttraumatic stress disorder and symptoms (Eisenberg et al, 2022; Krantz et al, 2022; Meinhausen et al, 2022), poor sleep quality and quantity (Meinhausen et al, 2022; Park & Kim, 2022), attention-deficit/hyperactivity disorder (Xu et al, 2022), and behavioral flexibility (Habibović et al, 2022)—all of which identify candidate treatment targets for future intervention studies.…”
Section: We Need To Refocus Our Science On the Clinical Research And ...mentioning
confidence: 99%
“…Our field has identified novel behavioral and psychosocial risk and prognostic factors for multiple CVD presentations and plausible mechanisms through which these factors could influence the development and course of CVD. Examples that reflect the ongoing evolution and expansion of the field’s focus are the articles in this issue on posttraumatic stress disorder and symptoms (Eisenberg et al, 2022; Krantz et al, 2022; Meinhausen et al, 2022), poor sleep quality and quantity (Meinhausen et al, 2022; Park & Kim, 2022), attention-deficit/hyperactivity disorder (Xu et al, 2022), and behavioral flexibility (Habibović et al, 2022)—all of which identify candidate treatment targets for future intervention studies.…”
Section: We Need To Refocus Our Science On the Clinical Research And ...mentioning
confidence: 99%
“…Thus, more work is needed to identify the mechanisms through which neighborhood factors affect health behaviors. Finally, Habibović et al (2022) found that behavioral flexibility (i.e., adaptive behavior change in response to the environment) had a small effect on CVD-related health behaviors (e.g., diet, physical activity, and stress management) among patients with hypertension or CVD.…”
mentioning
confidence: 98%